Study of dispersion characteristics and flame propagation, deflagration reaction behaviours of vapor liquid two-phase anhydrous hydrazine and DT-3/air mixtures - Xu, Fei-yang; Kang, Li-min; Cui, Ning; Yao, Ya-dong; Lei, Kang; Ma, Teng; Luo, Yi-min; Xu, Sen; Wu, xing-liang; Li, Yu-yan (International journal of hydrogen energy, 2025)
The knowledge of the vapor-liquid two-phase anhydrous hydrazine and DT-3 liquid propellant/air mixtures (mist) on the characterization of spatial and temporal distribution and the deflagration parameters are an essential subject in prevention of chain explosion accidents. To investigate the hazardous characteristics of detonable aerosols composed of anhydrous hydrazine and DT-3/air mixtures, a combined smooth particle hydrodynamics/finite element method (SPH/FEM) model and fuel-air-explosives (FAE) method were employed. The study focused on anhydrous hydrazine and DT-3/air clouds of varying sizes (5 and 10 kg). The results showed that, firstly, the sprays of fuels obtained a maximum lateral velocity and acceleration within 1 ms and velocity of that was on the order of 550 m s−1. The fuel droplets then underwent the stages of deceleration and free diffusing successively before forming vapor cloud (aerosol) and ultimately acquired explosive properties. The average explosion TNT equivalents of anhydrous hydrazine/air mixtures with masses of 5 and 10 kg were 6.16 and 2.08 times greater than that of DT-3 aerosol. Moreover, the maximum flame propagation velocity of 5 and 10 kg anhydrous hydrazine cloud were significantly higher than that of DT-3 aerosol at the same mass. The above fact indicated that mists of combustible anhydrous hydrazine in air was capable of detonating, furthermore, the reaction intensity of anhydrous hydrazine/air mixed system was significantly stronger than that of DT-3 vapor cloud. The average TNT equivalent of 10 kg anhydrous hydrazine and DT-3 cloud cluster was 1.18 and 3.49 times higher than the corresponding 5 kg fuel aerosol, respectively. When the mass of DT-3 aerosol increased from 5 to 10 kg, the response changed from combustion to deflagration, even weak detonation. Obviously, the mass influence on the reaction degree of liquid propellant/air mist was particularly significant. The achievements in current work are expected to provide a key data support for the safety distance setting of related building facilities such as the production and use of liquid propellants. •The diffusion microscopic characteristic of kilogram-level anhydrous hydrazine and DT-3 were elucidated.•The flame propagation law, deflagration reaction behaviours of anhydrous hydrazine and DT-3/air mixtures aerosols were probed.•The hazardous characteristics resulting from accidental leakage of liquid propellant mixing with air (from a several kilogram to tens kilogram) were effectively assessed.